Prevalence of pneumatization of the articular eminence and glenoid fossa viewed on cone-beam computed tomography examinations in a Turkish sample - NAMDAR PEKİNER, FİLİZ MEDİHA (SPRINGER, 2020)
Objective The aim of this study is to evaluate the prevalence of the pneumatization of the articular eminence and glenoid fossa (PAT and PGF, respectively) using cone-beam computed tomography (CBCT). Methods CBCT images of 1000 patients (511 females and 489 males) representing 2000 regions of interest (the glenoid fossa and articular eminence of each patient) were examined retrospectively with regard to age, gender, laterality, and type of pneumatization. The mean age of the female patients was 39.66 and that of males was 39.79. Suitable images from patients aged 16 years and over found in the archives of CBCT images were included in the study. The data were assessed using IBM SPSS 20 and statistical comparisons between two categorical variables were conducted using Chi square tests. Results It was observed that 14.7% of the patients had PAT and 47.1% had PGF. There was no significant difference in PAT and PGF prevalence between ages, age ranges, and gender in our study (p > 0.5). Conclusions It is important to evaluate the pneumatic cells in the articular eminence and glenoid fossa regions before surgery. It was also found that CBCT is more helpful in detecting pneumatization than plain film.
Keywords: Temporal bone; Pneumatization; Articular eminence; Glenoid fossa; Cone-beam computed tomography; TEMPORAL BONE PNEUMATIZATION; CELL DEFECT ZACD; MASTOID PNEUMATIZATION; MANAGEMENT